On the Non-Optimality of Information: An Analysis of the Welfare Effects of Anticipated Shocks in the New Keynesian Model - Hans-Werner Wohltmann; Roland C. Winkler (Kiel University, Department of Economics, 2008)
This paper compares the welfare effects of anticipated and unanticipated cost-push shocks in the canonical New Keynesian model with optimal monetary policy. We find that, for empirically plausible degrees of nominal rigidity, the anticipation of a future cost-push shock leads to a higher welfare loss than an unanticipated shock. A welfare gain from the anticipation of a future cost shock may only occur if prices are sufficiently flexible. We analytically show that this surprising result holds although unanticipated shocks lead to higher negative impact effects on welfare than anticipated shocks.
Keywords: E52; E32; E31; 330; Anticipated Shocks; Optimal Monetary Policy; Sticky Prices; Welfare Analysis; Kosten; Schock; Erwartungstheorie; Geldpolitik; Preisrigidität; Wohlfahrtseffekt; Theorie